Engineering coking resistant catalysts for CO2 utilisation: effects of catalyst composition - Li, Jiang Rong (Nanyang Technological University, 2023)
Catalysts made coking-resistant because of interplay between oxide and carbide species on the surface. Illustrated how VC-100 structure evolves under a given chemical potential of oxygen.